Synthesis, in vitro and in vivo biological evaluation, COX-1/2 inhibition and molecular docking study of indole-N-acylhydrazone derivatives. Issue 20 (1st November 2018) - Moraes, Ana Daura Travassos de Oliveira; Miranda, Mirelly Dianne Santos de; Jacob, Íris Trindade Tenório; Amorim, Cézar Augusto da Cruz; Moura, Ricardo Olímpio de; Silva, Simone Ângela Soares da; Soares, Milena Botelho Pereira; Almeida, Sinara Mônica Vitalino de; Souza, Túlio Ricardo Couto de Lima; Oliveira, Jamerson Ferreira de; Silva, Teresinha Gonçalves da; Melo, Cristiane Moutinho Lagos de; et al.
Graphical abstract: Abstract: The objective of this work was to obtain and evaluate anti-inflammatory in vitro, in vivo and in silico potential of novel indole- N -acylhydrazone derivatives. In total, 10 new compounds (3a –j ) were synthesized in satisfactory yields, through a condensation reaction in a single synthesis step. In the lymphoproliferation assay, using mice splenocytes, 3a and3b showed inhibition of lymphocyte proliferation of 62.7% (±3.5) and 50.7% (±2), respectively, while dexamethasone presented an inhibition of 74.6% (±2.4). Moreover, compound3b induced higher Th2 cytokines production in mice splenocytes cultures. The results for COX inhibition assays showed that compound3b is a selective COX-2 inhibitor, but with less potency when compared to celecoxib, and compound3a not presented selectivity towards COX-2. The molecular docking results suggest compounds3a and3b interact with the active site of COX-2 in similar conformations, but not with the active site of COX-1, and this may be the main reason to the COX-2 selectivity of compound3b . In vivo carrageenan-induced paw edema assays were adopted for the confirmation of the anti-inflammatory activity. Compound3b showed better results in suppressing edema at all tested concentrations and was able to induce an edema inhibition of 100% after 5 h of carrageenan injection at the 30 mg kg −1 dosage, corroborating with the COX inhibition and lymphoproliferation results. I addition to our experimental results, in silico analysis suggest that compounds3a and3b present a well-balanced profile between pharmacodynamics and pharmacokinetics. Thus, our preliminary results revealed the potentiality of a new COX-2 selective derivative in the modulation of the inflammatory process.